EU Smart City Governance - Gargiulo, Carmela; Pinto, Valentina; Zucaro, Floriana (TeMA - Journal of Land Use, Mobility and Environment, 2013)
In recent years European Commission has developed a set of documents for Members States tracing, directly or indirectly, recommendations for the transformation of the European city. The paper wants to outline which future EU draws for the city, through an integrated and contextual reading of addresses and strategies contained in the last documents, a future often suggested as Smart City. Although the three main documents (Cohesion Policy 2014-2020 of European Community, Digital Agenda for Europe and European Urban Agenda) face the issue of the future development of European cities from different points of view, which are respectively cohesion social, ICT and urban dimension, each of them pays particular attention to urban and territorial dimension, identified by the name of Smart City. In other words, the paper aims at drawing the scenario of evolution of Smart Cities that can be delineated through the contextual reading of the three documents. To this end, the paper is divided into three parts: the first part briefly describes the general contents of the three European economic plan tools; the second part illustrates the scenarios for the future of the European city contained in each document; the third part seeks to trace the evolution of the Smart Cities issue developed by the set of the three instruments, in order to provide the framework of European Community for the near future of our cities.